Redox metabolism correlates with cellular turnover and clinical phenotype of papillary thyroid carcinoma and colloid goiter - Branislav Rovcanin; Kristina Gopcevic; Dusan Kekic; Vladan Zivaljevic; Aleksandar Diklic; Svetislav Tatic; Milan Jovanovic; Bozidar Odalovic; Ivan Paunovic (Archives of Medical Science, 2019)
Introduction Papillary thyroid carcinoma (PTC) and colloid goiter (CG) represent the most common thyroid malignant and benign diseases, respectively. Oxidative stress is considered to have an important role in the pathogenesis of both diseases, but without sufficient and comprehensive data. The aim was to evaluate the redox profile, its influence on cell survival of PTC, comparing it with CG as a control and its relation with demographic, pathological and clinical parameters.